A COMPARATIVE STUDY OF INTRALESIONAL TRIAMCINOLONE ACETONIDE, 5- FLUOROURACIL AND THEIR COMBINATION FOR TREATMENT OF KELOIDS - Dr.Varsha Singh; Dr. Swati Gupta; Dr. Kapil Arora; Dr. Tarang Goyal; Dr. Amit Jaiswal (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background:The benign fibrous tissue growth that develops from an aberrant healing process in response to cutaneous injuries extending beyond the primary site of trauma/lesion or inflammatory response is called keloid. Multiple treatments have been tried and it’s still a concern for dermatologists to tell which the best modality for treating keloid. The current study evaluates the effect of intralesional triamcinolone acetonide and 5-FU either alone or in combination on various symptoms of keloid such as tenderness, pruritus, vascularity, telangiectasia, pliability, pigmentation, and dimensions.Aim & Objectives: To study and compare the therapeutic efficacy of intralesional triamcinolone acetonide, 5- fluorouracil and their combination keloids treatment in terms of clearance of lesions, side effects due to therapy and recurrence, if any on follow up.Material and Methods: This study was done among 60 patients of keloid in Muzaffarnagar Medical College & Hospital, Muzaffarnagar, Uttar Pradesh. Study was conducted for 12 months. Data was analysed statistically using mean, standard deviation and ANOVA test. Results: The participants in this study ranged from 10-70 years old. TAA had adverse effects in 12 patients, 5- FU had adverse effects in 10 patients while TAA + 5 FU (combination treatment) had adverse effects only in 08 patients. There is difference between the treatment TAA and 5-FU & also between 5 FU and TAA + 5 FU at the end of 30th week. But there is no significant difference between TAA and TAA+ 5 FU which concludes that these both are superior to 5 FU. But between TAA and combined treatment (TAA+ 5 FU), combination treatment is better than TAA having less average mean.Conclusion: So, we finally concluded that overall combination treatment was better than TAA and 5 FU alone in terms of both better result and less adverse effects.